La didáctica especial y su incidencia en el desarrollo cognitivo implementado en el aula taller de la carrera de parvularia de la Universidad Técnica de Cotopaxi, sector Eloy Alfaro, del cantón Latacunga, provincia de Cotopaxi, año lectivo 2011-2012 - Gualpa Sarabia, Vilma Salomé (2014)
The main objective of the special didactic is improve teaching techniques for a better cognitive development for each one of the students. It allows to correct the deficiencies in the education, improving teaching methods to enhance the ability of reasoning of the pupils. The methodology applied for learning must be new and innovative which will allow to be a fun education for improvement of the assimilation of the teaching given by the educator. This knowledge will be taken through the special didactics which might be practical or theoretical education. In conclusion the special didactics improves learning through an effective reasoning and cognitive development of each learners since education is recreated, defined with new methods and techniques of learning to the learner is recommended the use of new and innovative techniques and methods which will allow to improve the reception of the imparted teaching since it improves the learning style helping thus to socialize improving the new processes of teaching how important is to the learner to effective knowledge.